EAACI Allergen Immunotherapy User's Guide. (21st May 2020) - Alvaro‐Lozano, Montserrat; Akdis, Cezmi A.; Akdis, Mubeccel; Alviani, Cherry; Angier, Elisabeth; Arasi, Stefania; Arzt‐Gradwohl, Lisa; Barber, Domingo; Bazire, Raphaëlle; Cavkaytar, Ozlem; Comberiati, Pasquale; Dramburg, Stephanie; et al.
Abstract: Allergen immunotherapy is a cornerstone in the treatment of allergic children. The clinical efficiency relies on a well‐defined immunologic mechanism promoting regulatory T cells and downplaying the immune response induced by allergens. Clinical indications have been well documented for respiratory allergy in the presence of rhinitis and/or allergic asthma, to pollens and dust mites. Patients who have had an anaphylactic reaction to hymenoptera venom are also good candidates for allergen immunotherapy. Administration of allergen is currently mostly either by subcutaneous injections or by sublingual administration. Both methods have been extensively studied and have pros and cons. Specifically in children, the choice of the method of administration according to the patient's profile is important. Although allergen immunotherapy is widely used, there is a need for improvement. More particularly, biomarkers for prediction of the success of the treatments are needed. The strength and efficiency of the immune response may also be boosted by the use of better adjuvants. Finally, novel formulations might be more efficient and might improve the patient's adherence to the treatment. This user's guide reviews current knowledge and aims to provide clinical guidance to healthcare professionals taking care of children undergoing allergen immunotherapy.